Librarian Strategies to Enhance Students’ Reading Habits at SD Negeri 33 Banda Aceh - Zikrayanti ZIkrayanti; Nurrahmi Nurrahmi; Farah Hijriani; Wardatul Humairah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aims to evaluate the effectiveness of librarian strategies in enhancing students’ reading habits at SD Negeri 33 Banda Aceh. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation. The research subjects consisted of one librarian and twelve students selected through purposive sampling. The findings reveal that the librarian implemented various strategies, including routine library visits, provision of updated book collections, creation of a conducive reading environment, a 15-minute literacy program, a mobile reading cart, and classroom reading corners. Students generally responded positively to these strategies, although some expressed the need for more engaging book selections. The primary challenge identified was the limited number of library staff, which affected program consistency and book variety. Overall, the strategies demonstrated a positive impact, though further support and development are necessary to optimize their effectiveness.